2018
DOI: 10.1002/eat.22936
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of dissatisfaction, overvaluation and preoccupation with weight and shape for predicting onset of disordered eating behaviors and depressive symptoms over 15 years

Abstract: Objective The aim of this study was to examine the relative importance of dissatisfaction, overvaluation and preoccupation with body weight and shape in predicting increases in disordered eating behaviours and depressive symptoms from adolescence through to early adulthood. Method The study involved 1,830 participants (60% female) who completed the Project EAT survey during adolescence (mean age = 14.90 years, SD = 1.65 years) and again, 15 years later, in early adulthood. Participants provided assessments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
71
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 38 publications
11
71
2
2
Order By: Relevance
“…The results of our study suggest that similar to thinness‐oriented concerns (e.g., Sharpe et al, ), a drive for muscularity may represent a unique and important pathway through which ED symptoms may manifest. The drive to enhance the visibility of muscle may precipitate unhealthy cognitions and behaviors where fat loss is a primary goal (Lavender et al, ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The results of our study suggest that similar to thinness‐oriented concerns (e.g., Sharpe et al, ), a drive for muscularity may represent a unique and important pathway through which ED symptoms may manifest. The drive to enhance the visibility of muscle may precipitate unhealthy cognitions and behaviors where fat loss is a primary goal (Lavender et al, ).…”
Section: Discussionsupporting
confidence: 71%
“…However, shifts in women's appearance ideals toward greater muscular leanness bring about new research questions regarding the potential costs of pursuing these ideals. For example, Rodgers et al () recently found associations between the desire to be toned with body image concerns and a drive for thinness among college women, both of which are important risk factors for eating‐disorder (ED) pathology (McLean & Paxton, ; Sharpe et al, ). Given that a crucial aspect of the toned ideal is possessing minimal body fat to enhance the visibility of muscularity, it is reasonable to suspect women with a desire to increase muscle tone may engage in ED behaviors to reduce adiposity (e.g., caloric restriction; Murray, Griffiths, & Mond, ).…”
mentioning
confidence: 99%
“…However, it is contradictory to a cross-sectional study that reported a lack of relationship between body dissatisfaction and depressive symptoms among Black adolescents mixed of healthy weight and overweight/obese status [35]. The positive relation between antecedent body dissatisfaction and later depressive symptoms supports the "thinness ideal theory" that overweight/obesity increases body dissatisfaction, and the weight-related concern or pressure [ 21,58] in turn leads to depressive symptoms [25,27]. Future studies need to assess whether the relation holds among Black adolescents from middle-class families who may have mothers with a lower prevalence of overweight/obesity.…”
Section: Discussionmentioning
confidence: 75%
“…A discrepancy between ideal weight or shape and actual weight or shape can result in body dissatisfaction, which leads to depressive symptoms [20]. This theory has been supported by longitudinal studies that reported body dissatisfaction as a risk factor for subsequent depressive symptoms [22][23][24][25][26][27]. However, a reverse relation has also been proposed.…”
Section: Introductionmentioning
confidence: 89%
“…Body image has been found to influence day-to-day functioning, mental health, psychopathology (e.g. feelings of shame, depression, and anxious thoughts [4]), selfesteem, social interactions and quality of life [5,6,7]. Disturbance of the perceptual component, body image distortion (BID) is the discrepancy between ones' actual body size and the perception of their own body size.…”
Section: Body Image Distortion (Bid)mentioning
confidence: 99%